Cumulative effects of noise and odour annoyances on environmental and health related quality of life. (December 2015) - Oiamo, Tor H.; Luginaah, Isaac N.; Baxter, Jamie
Abstract: Noise and odour annoyances are important considerations in research on health effects of air pollution and traffic noise. Cumulative exposures can occur via several chemical hazards or a combination of chemical and stressor-based hazards, and related health outcomes can be generalized as manifestations of physiological and/or psychological stress responses. A major research challenge in this field is to understand the combined health effects of physiological and psychological responses to exposure. The SF-12 Health Survey is a health related quality of life (HRQoL) instrument designed for the assessment of functional mental and physical health in clinical practice and therefore well suited to research on physiological health outcomes of exposure. However, previous research has not assessed its sensitivity to psychological stress as measured by noise annoyance and odour annoyance. The current study validated and tested this application of the SF-12 Health Survey in a cross-sectional study (n = 603) that included exposure assessment for traffic noise and air pollution in Windsor, Ontario, Canada. The results indicated that SF-12 scores in Windsor were lower than Canadian normative data. A structural equation model demonstrated that this was partially due to noise and odour annoyances, which were associated with covarying exposures to ambient nitrogen dioxide and traffic noise. More specifically, noise annoyance had a significant and negative effect on both mental and physical health factors of the SF-12 and there was a significant covariance between noise annoyance and odour annoyance. The study confirmed a significant effect of psychological responses to cumulative exposures on HRQoL. The SF-12 Health Survey shows promise with respect to assessing the cumulative health effects of outdoor air pollution and traffic noise. Highlights: Noise and odour annoyances proposed as indicators of coping with ambient stressors. Confirm air pollution and traffic noise interaction effect on annoyances. Demonstrate cumulative effects of annoyances on functional health and wellbeing.